Environmentalists abide: Listening to whale music – 1965–1985. (December 2017) - Ritts, Max
Music can enrich geographical efforts to understand ideology as a lived experience. This paper explores the history of whale music – instrumental music that samples or thematizes whale sound. For environmentalists who came of age in the late 1960s, whale music fostered new interrogations about the identity of nature and the nature of identity, interrogations that reflected structural changes in North American society. To understand whale music's surprising ideological power, I draw on Althusser's formative idea of interpellation, and refine it with insights from Antonio Gramsci, John Mowitt, and Neil Smith. As examples from British Columbia's Lower Mainland and California's Bay Area reveal, whale music interpellated environmentalists, capturing the energies of predominantly white middle-class subjects eager to develop new relationships with nature. Whale music was not discovered, as its devotees proposed it was, but invented, through a combination of animal sounds, recording techniques, consumer trends, and ideologies of nature. It reveals environmentalism as a sonorous formation – a system that recruits listeners into sonically-mediated realms of thought, action, and subjectivity.